Software Project Management: A Practical Guide to manage Small Software Development Project. - Abd Ghani, M. K. (Penerbit UTeM, 2011)
The objective of this book to provide guidance, tips, experiences and lessons learned to young software developer on how to managing a software development project. The software developer will learn the management skills through the real problems highlighted in the case study of this book.